2018
DOI: 10.1038/s41598-018-26700-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining micro-RNA and protein sequencing to detect robust biomarkers for Graves’ disease and orbitopathy

Abstract: Graves’ Disease (GD) is an autoimmune condition in which thyroid-stimulating antibodies (TRAB) mimic thyroid-stimulating hormone function causing hyperthyroidism. 5% of GD patients develop inflammatory Graves’ orbitopathy (GO) characterized by proptosis and attendant sight problems. A major challenge is to identify which GD patients are most likely to develop GO and has relied on TRAB measurement. We screened sera/plasma from 14 GD, 19 GO and 13 healthy controls using high-throughput proteomics and miRNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 66 publications
4
35
0
1
Order By: Relevance
“…[24] Although the biological activity of TWEAK is complex, it is known to be activated in inflammatory autoimmune disease and may serve as a reliable diagnostic and prognostic biomarker. Identifying new biomarkers and therapeutic targets other than TSHR for GD and GO by combining microRNA and protein sequencing [25] can improve our understanding of the pathogenesis of these disorders and lead to the development of effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Although the biological activity of TWEAK is complex, it is known to be activated in inflammatory autoimmune disease and may serve as a reliable diagnostic and prognostic biomarker. Identifying new biomarkers and therapeutic targets other than TSHR for GD and GO by combining microRNA and protein sequencing [25] can improve our understanding of the pathogenesis of these disorders and lead to the development of effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that urinary 8-hydroxy-2-deoxyguanosine (8-OHdG), an oxidized nucleoside of DNA, is a DNA oxidative stress biomarker and a risk factor for cancer, atherosclerosis, and diabetes (Wu et al, 2004; Kawai et al, 2018). In diabetic patients with hyperglycemia, increased urinary 8-OHdG and leukocyte DNA has been reported, and the urinary 8-OHdG level in diabetes patients has been linked with the severity of diabetic nephropathy and retinopathy (Zhang G. et al, 2018; Zhang L. et al, 2018; Zhang X. G. et al, 2018). Various methods, including high-performance liquid chromatography (HPLC), with and without extraction, and enzyme-linked immunosorbent assays (ELISAs), are proposed to determine 8-OHdG in tissues and urine (Wu et al, 2004; Kawai et al, 2018).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…Another study revealed that lysozyme is related to circulating RNA, extracellular vesicles, and chronic stress (Abey et al, 2017). Currently lysozyme as diagnostic biomarker has found applications in chronic stress (Abey et al, 2016), cancer metastasis (Brzozowski et al, 2018), cardiovascular markers, psychological research (Mishra, 2017), oral diseases (Lorenzo-Pouso et al, 2018), diabetes (Maciejczyk et al, 2017), wound healing (Abey et al, 2016), infectious diseases (Ghosh et al, 2018; Stjärne Aspelund et al, 2018), Graves' disease and orbitopathy (Zhang L. et al, 2018). Serum lysozyme has been used as a clinical biomarker for diagnosing sarcoidosis with high specificity (Ramos-Casals et al, 2019).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…This is a relatively recent research field that could explain the different penetrance of genetic susceptibility, and could also represent the mechanism of interaction between genetic predisposition and environmental factors [127]. The analysis of miRNA, alone or associated with proteomics, has also an interesting potential as biomarker of TA, especially GD [128].…”
Section: Graves' Diseasementioning
confidence: 99%